Characteristics and Antibacterial Activities of Bacteriocin Produced by Lactid Acid Bacteria Isolate LG-50 and LG-90 - Putri, Thalitha Nindika Nathania; Kusharyati, Dyah Fitri; Ryandini, Dini (Fakultas Biologi Universitas Jenderal Soedirman, 2023)
Biopreservative agents is natural food preservative agent derived from microbes such as bacteriocin produced by lactic acid bacteria (LAB). Bacteriocin is a protein compound that has a small molecular weight and has antibacterial activity because it is effective in preventing the growth of pathogenic bacteria in food and beverages. Escherichia coli and Staphylococcus aureus are pathogenic bacteria that can contaminate seafood products because they can cause infection and food toxication. Isolates LG-50 and LG-90 are LAB, bacterial collection of the Microbiology Laboratory, Faculty of Biology, Isolate from mangrove sediment in Logending beach. Both isolates are not yet known for their potencies to synthesize bacteriocin and its inhibitory capability to the growth E. coli and S. aureus. The research aimed to determine the ability of LG-50 and LG-90 isolates to produce bacteriocin, to determine the ability of LG-50 and LG-90 isolates to inhibit the growth of E. coli and S. aureus bacteria invitro, to identity the characteristics of isolate LG-50 and LG-90 from Logending beach mangrove sediment. The results of this research show that the bacteriocins LG-50 and LG-90 were able to inhibit the growth of E.coli with inhibition zone diameters of 13.5 mm and 13 mm, in S. aureus with inhibition zone diameters of 15 mm and 15.5 mm.